2015
DOI: 10.1080/15592294.2015.1073881
|View full text |Cite
|
Sign up to set email alerts
|

Placental expression profile of imprinted genes impacts birth weight

Abstract: The importance of imprinted genes in regulating feto-placental development has been long established. However, a comprehensive assessment of the role of placental imprinted gene expression on fetal growth has yet to be conducted. In this study, we examined the association between the placental expression of 108 established and putative imprinted genes and birth weight in 677 term pregnancies, oversampled for small for gestational age (SGA) and large for gestational age (LGA) infants. Using adjusted multinomial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 28 publications
4
89
0
Order By: Relevance
“…Furthermore, the DNA methylation at these imprinted genes are resistant to a second epigenetic reprogramming event, which occurs in the pronuclei of the fertilized oocyte immediately after fertilization (Messerschmidt et al, 2014). The integrity of DNA methylation patterns at these imprinted genes is thought to be vital to the embryo as these genes are important for growth and development during pregnancy (Kappil et al, 2015). Altogether, DNA methylation appears to play a fundamental role in healthy germline development and spermatogenesis, as well as a possible role in offspring development via the inheritance of DNA methylation from spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the DNA methylation at these imprinted genes are resistant to a second epigenetic reprogramming event, which occurs in the pronuclei of the fertilized oocyte immediately after fertilization (Messerschmidt et al, 2014). The integrity of DNA methylation patterns at these imprinted genes is thought to be vital to the embryo as these genes are important for growth and development during pregnancy (Kappil et al, 2015). Altogether, DNA methylation appears to play a fundamental role in healthy germline development and spermatogenesis, as well as a possible role in offspring development via the inheritance of DNA methylation from spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…This syndrome has been proven to be epigenetically and phenotypically similar to epigenetic Beckwith-Wiedemann's syndrome in humans, which also seems to occur more often after IVF conception [19]. Besides, placental expression of certain imprinted genes has already been connected to altered LGA risk in term pregnancies [20].…”
Section: Introductionmentioning
confidence: 99%
“…Nine imprinted genes were positively associated with large for gestational age (LGA) status, including MEST, BLCAP,H19,NDN,PLAGL1,DLK1,IGF2,MEG3 and NNAT, in an order of decreased odds ratio. MEST expression was negatively associated with a risk of SGA status, suggesting it as a novel biomarker for analyzing postnatal health outcomes (Kappil et al 2015). Another study group found four downregulated genes (CDKAL1, DHCR24, PLAGL1 and ZNF331) and five upregulated genes (CCDC86, ILK, NNAT, PEG10 and PHLDA2) in the FGR placentas of human.…”
Section: Imprinted Genes and Epigenetic Changes Are Involved In The Cmentioning
confidence: 99%
“…www.reproduction-online.org was mediated by the up-regulation of MMP-2, MMP-9 and TIMP-1 (Chen et al 2015). Significantly decreased invasive ability and migration were observed in EVT by knocking down the maternally imprinted gene MEST in HTR8/SVneo cells.…”
Section: R234mentioning
confidence: 99%